Press-Public Collaboration as Infrastructure: Tracing News Organizations and Programming Publics in Application Programming Interfaces. (May 2013) - Ananny, Mike
Understanding and evaluating systems for open collaboration depends, in part, on appreciating their normative and institutional contexts. In this article, I examine press-public collaboration by tracing how and why news organizations both distance themselves from and depend on networked actors outside the newsroom to achieve professional and organizational goals. I situate contemporary press-public networks within infrastructure scholarship, review their relationship to models of the public sphere, and trace the motivations and assumptions embedded within news organizations' application programming interfaces, software toolkits that let those outside the newsroom access and repurpose journalistic data.